Proposal for the Production and Marketing of Beekeeping Products - María Fernanda Miranda Salazar; Diana Katherine Campoverde Santos; Luis Antonio Velasco Matveev (ESPOCH Congresses, 2022)
Abstract This research was carried out due to the growing interest in the consumption of natural and healthy products. The COVID-19 pandemic has affected, in some way, all types of business around the world, including beekeeping. The study utilized an inductive–deductive method to analyze the variables of consumption, preferences, costs, etc. Data were collected in the city of Riobamba through a survey of 382 people over 18 years of age. Several aspects were considered such as quality, availability, price, representation, and distribution. The instrument applied was a structured questionnaire with 10 closed questions. The results obtained from the analysis and interpretation of the information were favorable and it was determined that 67% of those surveyed consumed bee products, of which 35% were interested in consuming only bee honey. The frequency of consumption was weekly in 65% of them while others consumed it every two weeks or monthly. The most consumed quantity was 100 grams by 59% of the respondents, of whom 27% bought honey through health food stores while 23% from supermarkets. Moreover, 31% of the respondents considered the quality of the product while making the purchase and 37% preferred to obtain product information through social networks.